A Comparative Analysis of Cost Escalation, Quality Degradation in Road Construction - Satheesh, Pratheeksha; Daimari, Kamathenu (Journal of Progress in Civil Engineering, 2025)
Corruption in public infrastructure projects, particularly road construction, inflates costs, reduces quality, and undermines development. This research paper develops a corruption index by comparing per - kilometer road construction costs across countries, adjusted for Purchasing Power Parity (PPP), and evaluates road quality. Using data from government reports, international organizations, and peer - reviewed studies, the paper identifies significant disparities in costs and quality, and explores the underlying factors, including governance, transparency, and institutional quality. The findings highlight the need for stronger anti - corruption measures and improved accountability in infrastructure projects.